ANALISIS KERAGAMAN GENETIK PADA IKAN KERAPU MACAN (Epinephelus fuscoguttatus) YANG TAHAN TERHADAP PENYAKIT YANG DISEBABKAN BAKTERI Vibrio alginolyticus - Triana, St. Hidayah; Gani, Mahir S.; Malina, Asmi Citra (Torani Journal of Fisheries and Marine Science, 2014)
The research was purposed to analyse genetic similarity of tiger grouper (Epinephelus fuscoguttatus) inorder to select grouper that was resistant to Vibrio alginolyticus. In this study, fish were challenged with Vibrioalginolyticus and genetic similarity was examined by a PCR-RAPD method. Eight RAPD primers were used forPCR-RAPD analysis. The results showed that only three primers of RAPD primer (YNZ-22, UBC-456, danUBC-457) generated high number of RAPD fragments. The resistant group of tiger groupers generated higherpolymorph RAPD fragments than the susceptible groups. RAPD primer YNZ-22 and UBC-457 generated 82 %and 71 % of RAPD polymorph fragments from resistant group of fish and 71% and 60 % from susceptiblegroups, respectively. Primer YNZ-22 is a best genetic marker to analyse genetic similarity of tiger groupersproduced specific marker ranging from 1,2-2,0 kb. Genetic distances between the population of resistant fishand population of susceptible fish was 0.5091 and between individual of the resistant fish and susceptible fishwas 0.7032. Keywords: Genetik diversity, Epinephelus fuscoguttatus, V. alginolyticus, PCR, RAPD.